Preliminary Study of Growth and Yields of Eucalyptus Species at Afaka, a Typical Northern Guinea Savanna - Adegbehin, J. O.; Asiribo, O. E. (Indian Forester, 2002)
Trial plantings of exotic tree species commenced in the Savanna Region of Northern Nigeria over 50 years ago. Based on data from permanent sample plots, site index curves and yield tables were constructed for the promising Eucalyptus species, viz. E. cloeziana, E. citriodora, E. camaldulensis and E. tereticornis at Afaka, a typical Northern Guinea Savanna Zone of Nigeria. From the guiding (average site) curves constructed, the results revealed that at a reference age of 10 years E. cloeziana, E. citriodora and E. camaldulensis attained a top height of about 24.6m, 23.6m, and 21.5m respectively while E. tereticornis had 4 site classes viz: I (25.3m); II (21.7m) III (18.1m) and IV (I4.6m) at a reference age of 10 years. The yield figures derived from the yield classes resulting from the constructed site index curves revealed the maximum mean current annual increment (MCAI), the maximum mean annual increment (MMAI), total volume production at the point of maximum current annual increment (VMCAI) and the total volume production at the point of maximum mean annual increment (VMMAI) as follows.